KARAKTERISTIK LEMBAGA KONSINYASI DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Tantri Noviana Herawati; Ghansham Anand (Fakultas Hukum Universitas Gresik, 2018)
The social function of land has become one of the basis for GovernmentÃ¢â‚¬â„¢s policy to put public interest on top of the individual ones, with regard to rights of the individuals. The main purpose of land procurement for public interest is to provide land for the development, in order to increase the welfare and prosperity of the nation. Despite this notion, any legal interest of the parties concerned must still be guaranteed. To guard the public interest, it is necessary to give compensation to any rightsholder whose land has been acquisited by the government. The land procurement process shall be carried out in accordance with the legal regulations concerned, especially Law Number 2 of 2012 about Land Procurement for Public Utilities Construction. In case the rightsholder refuses to accept the form and/or the value of compensation that has been negotiated previously, the government regulated that the compensation shall be commended in a District Court. Ã‚Â Ã‚Â Keywords : Social Function, Compensation, Consignment.Ã‚Â Ã‚Â Ã‚Â ABSTRAKÃ‚Â Fungsi sosial tanah telah menjadi salah satu dasar kebijakan Pemerintah untuk menempatkan kepentingan publik di atas yang individu, berkaitan dengan hak-hak individu. Tujuan utama pengadaan tanah untuk kepentingan umum adalah menyediakan lahan untuk pembangunan, untuk meningkatkan kesejahteraan dan kemakmuran bangsa. Terlepas dari pengertian ini, setiap kepentingan hukum dari pihak-pihak terkait masih harus dijamin. Untuk menjaga kepentingan publik, perlu memberikan kompensasi kepada pemegang hak cipta yang tanahnya telah diakuisisi oleh pemerintah. Proses pengadaan tanah harus dilakukan sesuai dengan peraturan hukum yang bersangkutan, khususnya Undang-Undang Nomor 2 Tahun 2012 tentang Pengadaan Tanah untuk Pembangunan Utilitas Umum. Jika pemegang hak menolak untuk menerima nilai kompensasi yang telah dinegosiasikan sebelumnya maka pemerintah mengatur bahwa kompensasi akan dititipkan di Pengadilan Negeri. Ã‚Â Kata kunci: Fungsi Sosial, Kompensasi, Konsinyasi.